Social conflict : towards a methodological and theoretical position - Volbrecht, Glynda (Department of Sociology, 2016)
This study rests on the assumption that the methods of science embodied in the general canons of the scientific enterprise (particularly in relation to theory formulation and validation) constitute the realm of theoretical practice from which to develop a methodological and theoretical position relevant to the phenomenon of social conflict.